Application of the modal control method to an asynchronous drive - Yu. M. Kulinich; D. A. Starodubtsev (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. The development of power electronics and information technology facilitates the development and implementation of variable frequency electric drives for both traction motors and auxiliary machines of an electric locomotive. This publication is a continuation of research into controlling asynchronous machines of AC locomotives auxiliary electric drives (“Russian Railway Science Journal”, 2021, No. 5; 2022, No. 1; 2023, No. 1).Materials and methods. In order to simulate dynamic processes that occur in the modal controller of an asynchronous motor the authors used SimInTech software developed by 3V Service, a domestic vendor, that enables exploring the operation of an asynchronous drive using a simulation modeling technique.Results. It is established that the applied modal control method enables setting the time and nature of transient processes during an asynchronous motor control. The results of modeling a simulation of an automatic control system confirmed that the application of this method features long-term benefits.Discussion and conclusion. The presented outcomes of modeling an automatic control system for an asynchronous drive based on the modal control method revealed an opportunity to significantly reduce transient processes period. This is achieved through the use of delayless flux linkage and angular rotation speed feedback of the motor rotor in the modal controller.